Pest Detection Expert System And Method Using Bayes Rice Diseases - WAHYUN, WIWIN CINDYTIA; SITIO, ARJON SAMUEL (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Indonesia is included in an agricultural country that is rich in agriculture, fertile land in Indonesia allows for the growth of various types of plants, one of which is rice. But in the cultivation of rice plants, it will never be separated from pests and diseases of rice plants, so that the growth of rice plants is not optimal. Due to the large number of pests and diseases that can attack rice plants, it is necessary to take proper care in dealing with pests and diseases of rice plants to avoid losses that can result in reduced production of rice plants. Therefore an expert system was created which was expected to help farmers in consulting about diseases and pests contained in their rice plants to the experts without having to meet with experts directly. In its identification, the expert system for diagnosing ahama and rice disease uses the Bayes method and uses the Website in its implementation.